Prevalence and correlates of active traveling to school among adolescents in Cyprus - Loucaides, Constantinos A; Jago, Russell; Theophanous, Maria (Central European Journal of Public Health, 2010)
More data regarding prevalence and correlates of active travel to school are needed from different parts of the world. The purpose of this study was to examine prevalence and correlates of active travel to school among adolescents in Cyprus. A cross-sectional study was conducted among 1966 adolescents attending grade 6, grades 7-9, grades 10-12 and technical/vocational schools in Cyprus. Overall prevalence of active travel to school was 19.4%. Parental perceptions of safe route to school, other children walking to school from the child's neighborhood and school location (urban versus rural) were associated with active travel across different levels of education. Having enough time to walk to school in the moming was the most consistent correlate of active travel. Low prevalence estimates of active traveling to school among adolescents in Cyprus raise the need to promote this source of daily physical activity.
Keywords: Students; Cyprus; Female; charakteristiky bydlení; dítě; Urban Population; Age Factors; ženské pohlaví; Transportation; Adolescent; Rural Population; věkové faktory; lidé; cvičení; Residence Characteristics; venkovské obyvatelstvo; doprava; Male; Walking; městské obyvatelstvo; Kypr; Child; studenti; mužské pohlaví; Exercise; mladiství; chůze; Humans